2017
DOI: 10.1097/md.0000000000007836
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative intravenous glucocorticoids can reduce postoperative acute pain following total knee arthroplasty

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Even more interesting, the number of included trials varied between analyses. Thus, the included RCTs varied: n = 4 in [5]; n = 14 in [6]; n = 11 in [7]; n = 6 in [8]; n = 8 in [9]; n = 7 in [10]; n = 4 in [16]; and n = 9 in [17] A detailed assessment of the 28 RCTs included in the TKA-specific systematic reviews [5-10, 16, 17] is presented in Table 1. The trials included in the systematic reviews/ meta-analyses have considerable scientific flaws which make interpretation of these analyses challenging (Table 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Even more interesting, the number of included trials varied between analyses. Thus, the included RCTs varied: n = 4 in [5]; n = 14 in [6]; n = 11 in [7]; n = 6 in [8]; n = 8 in [9]; n = 7 in [10]; n = 4 in [16]; and n = 9 in [17] A detailed assessment of the 28 RCTs included in the TKA-specific systematic reviews [5-10, 16, 17] is presented in Table 1. The trials included in the systematic reviews/ meta-analyses have considerable scientific flaws which make interpretation of these analyses challenging (Table 1).…”
mentioning
confidence: 99%
“…Since 2015, a total of 12 systematic reviews/meta-analyses have been published on the analgesic effects of pre-operative glucocorticoid administration after joint arthroplasty [5][6][7][8][9][10][11][12][13][14][15][16]. Of these, only five [5,6,9,10,16] were prospectively registered and seven studies focused only on TKA [5][6][7][8][9][10]16], while five reviews combined trials of TKA and total hip arthroplasty (THA). The TKA-specific systematic reviews/meta-analyses [5][6][7][8][9][10]16] included all the TKA-related trials in the analyses from the combined THA/TKA reviews.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An equivalent dexamethasone dose less than 15 mg was identified as low dose and ≥15 mg was identified as high dose. [ 15 ] A P value less than .05 was considered statistically significant. Mixed meta-regression (methods of moment) was used to assess any potential interaction between dexamethasone dose (or equivalent) in the first 24 hours and the risk of PONV.…”
Section: Methodsmentioning
confidence: 99%
“…Final results indicated that intravenous glucocorticoid can decrease the VAS at 12 and 24 hours and by 8.41 points, 7.46 points, and 13.99 points, respectively, with clinical significance. Liu et al [ 22 ] identified that intravenous glucocorticoids may be as an effective and safe method to reduce postoperative pain in patients following TKA. Meng and Li [ 23 ] found that intravenous dexamethasone could significantly reduce postoperative pain scores following total joint arthroplasty (TJA).…”
Section: Discussionmentioning
confidence: 99%